Vanadate reduction by gram-positive fermentative bacteria isolated from deep-sea sediments on the northern Central Indian Ridge - Bokyung Kim; Dong Kyun Woo; Juhwan Jeong; Min Sub Sim (PLoS ONE, 2025)
The oxidation states of vanadium determine its mobility and toxicity, and dissimilatory vanadate reduction has been reported in several microorganisms, highlighting the potential significance of this pathway in the remediation of vanadium contamination and the biogeochemical cycle. However, to date, most known microorganisms capable of reducing vanadate are Gram-negative respiratory bacteria belonging to the phylum Proteobacteria. In this study, we isolated Tepidibacter mesophilus strain VROV1 from deep-sea sediments on the northern Central Indian Ridge and investigated its ability to reduce vanadium and the impact of vanadate on its cellular metabolism. A series of culture experiments revealed that the isolated strain efficiently reduces V(V) to V(IV) during fermentation, even at mM levels, and this reduction involves a direct biological process rather than indirect reduction via metabolic products. Vanadium affects microbial carbon and nitrogen metabolism. Notably, in the presence of vanadate, alanine production decreases, suggesting that metabolic flux is diverted from the transamination reaction to vanadate reduction. T. mesophilus VROV1 is the second Gram-positive bacterium identified to reduce vanadium, following Lactococcus raffinolactis, but these bacteria belong to different classes: T. mesophilus is classified as Clostridia, whereas L. raffinolactis is classified as Bacilli. The specific rate of vanadate removal by VROV1 was as high as 2.8 pmol/cell/day, which is comparable to that of metal-reducing bacteria and markedly exceeds that of L. raffinolactis. Our findings expand the distribution of vanadate-reducing organisms within the bacterial domain. Given the wide range of natural habitats of T. mesophilus and its close relatives, we speculate that fermentative vanadate reduction may have a greater impact on the global biogeochemical cycle of vanadium than previously thought.